Product Innovation and Start-Up Business Market Share Performance - Robinson, William T. (Management Science, 1990)
This empirical study estimates the impact of several product innovation attributes on initial market share. We find that the product's advantage relative to competing products has the strongest market share impact. Incompatibility with customers' existing way of doing things does not have a meaningful market share impact. By reducing market share, a new and proprietary product technology tends to act as a barrier to adoption, unless the effect is offset by a major product advantage.